The Question of Animal Ethics in Contemporary Art - Mirra Elísabet Valdísardóttir 1988- (2023)
This thesis has been presented for a BA-degree in Art Studies at the University of Iceland. It analyses the role of animal ethics in contemporary art from the second half of the 20th century to the present day. It asks what progress is being made towards the ethical improvement of animals and what hindrances continue to impede advancement away from a non-hierarchical species dominant realm of art. The topic of animal ethics will be explored and discussed from an artistic and philosophical viewpoint. As art ruminates in the midst of an anthropocentric epoch, the inclusion of the non-human animal is a key principle in the discussion at hand. Artists and researchers Bryndís Snæbjörnsdóttir and Mark Wilson will be discussed in depth, as well as the controversial work of Damien Hirst and Hermann Nitsch. I will also draw upon the theories of post-modernist writers including Jacques Derrida and John Berger, in context with a multitude of exhibitions contributing to the ethical discourse. These exhibitions encourage participants to evaluate their perspective and relationship with the marginalized animal kingdom, thus recreating a new aesthetic parallel. With the question of ethics in mind, the medium of art has the possibility of becoming a redeeming recourse that ends animal suffering in the name of aesthetic disposition.